2014
DOI: 10.1002/ajp.22273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ancestry on behavioral variation in two species of howler monkeys (Alouatta pigraandA. palliata) and their hybrids

Abstract: Social differences between primate species may result from both flexible responses to current conditions or fixed differences across taxa, yet we know little about the relative importance of these factors. Here, we take advantage of a naturally occurring hybrid zone in Tabasco, Mexico to characterize the variation in social structure among two endangered howler monkey species, Alouatta pigra and A. palliata, and their hybrids. Work in pure populations has suggested that A. pigra females maintain closer proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 74 publications
2
21
0
1
Order By: Relevance
“…A recent comparative behavioral study by Ho et al [2014] analyzing groups of both species near locations sampled in this study found that A. pigra females were in closer proximity to one another and had higher rates of affiliative behavior than A. palliata females; which ratifies the expected differences based on reports made by numerous behavioral studies on each species [Ho et al, 2014 and references therein]. These differences in social interactions would be expected if within-group A. pigra females were more closely related than A. palliata within-group females, but our study does not provide support for this inference, suggesting that kinship may not always be a strong determinant of social interactions among females.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative behavioral study by Ho et al [2014] analyzing groups of both species near locations sampled in this study found that A. pigra females were in closer proximity to one another and had higher rates of affiliative behavior than A. palliata females; which ratifies the expected differences based on reports made by numerous behavioral studies on each species [Ho et al, 2014 and references therein]. These differences in social interactions would be expected if within-group A. pigra females were more closely related than A. palliata within-group females, but our study does not provide support for this inference, suggesting that kinship may not always be a strong determinant of social interactions among females.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we examined locus-specific differentiation and introgression using reduced-representation sequencing data from a bimodal howler monkey hybrid zone (Alouatta palliata × Alouatta pigra) (Cortés-Ortiz et al, 2015) and from allopatric parental populations to test predictions about the forms of selection acting on loci associated with reproductive isolation. The parental species diverged ~3 Ma (Cortés-Ortiz et al, 2003) and have many important differences in their morphology (Kelaita, Dias, Aguilar-Cucurachi, Canales-Espinosa, & Cortés-Ortiz, 2011;Smith, 1970), cytogenetics (Steinberg et al, 2008), social systems (Chapman & Balcomb, 1998;Ho et al, 2014) and loud vocalizations (Bergman et al, 2016). Throughout most of their ranges, A. palliata and A. pigra are allopatric, but their ranges overlap in a narrow contact zone (~20 km, Cortés-Ortiz et al, 2007, Cortés-Ortiz et al, 2018 in Tabasco, Mexico (Figure 1).…”
mentioning
confidence: 99%
“…Hybrid zones provide the opportunity to explore reproductive strategies of individuals with very different genetic backgrounds (both pure and admixed) in the same ecological and social context (Bergman et al 2008 ). Ongoing studies on the social dynamics in the Mexican hybrid zone (e.g., Ho et al 2014 ) will allow us to evaluate the competitive abilities of hybrid versus purebred individuals. In Brazil, Aguiar ( 2010 ) conducted a study on social interactions in two mixed groups composed of pure A. caraya , A. guariba and putative hybrids.…”
Section: Interaction Between Social Dynamics and Hybridizationmentioning
confidence: 99%
“…Ever since its discovery , research on the anatomical and genetic bases of howler trichromacy has increased. However, the adaptive signifi cance of this trait remains unclear (Hernández- Salazar et al 2014 ). Extensive population-level studies of the distribution of L/M opsin genes and detailed fi eld observations of visual behaviors of howlers are important for elucidating whether trichromacy is related to an enhanced ability to locate orange-and redcolored fruits or young leaves, or to identify changes in the intensity skin and hair pigments as social/reproductive signals Melin et al 2014 ).…”
Section: Ontogeny and Sensory Ecology Of Howlersmentioning
confidence: 99%
See 1 more Smart Citation